Impact damage assessment of sandwich composite materials using non-destructive techniques - Tendai Chipanga (22571069) (2025)
This study examines the low-velocity impact response and damage tolerance of sandwich composites fabricated via the autoclave process. A detailed damage assessment was conducted on specimens comprising glass fibre-reinforced polymer (GFRP) and carbon fibre-reinforced polymer (CFRP) face sheets, with a polyvinyl chloride (PVC) foam core. Initial mechanical testing was performed to determine key material properties relevant to impact performance. Subsequent impact testing was carried out to evaluate damage behaviour under low-velocity conditions. Damage mechanisms were characterised using X-ray micro-computed tomography (micro-CT), a non-destructive technique that revealed matrix cracking, intra-laminar and inter-laminar delamination, fibre breakage, foam shearing, and densification across varying impact energy levels. BVID was shown to significantly reduce residual strength, thereby undermining structural integrity. ImageJ software was employed to validate the quality of the reconstructed CT images. To complement the experimental findings, a numerical study was conducted using nonlinear finite element (FE) analysis in Abaqus, integrated with a Fortran compiler. The computational framework incorporated a user-defined material subroutine (VUMAT) implementing 3D Hashin failure criteria. Notably, this study extended existing modelling approaches by integrating both ductile and shear damage into the PVC Crushable Plasticity model, an enhancement not commonly addressed in prior work. The inclusion of ductile damage enabled the simulation of progressive stiffness degradation due to plastic deformation, while shear damage was critical for capturing delamination and core-skin debonding phenomena. The foam core's post-yield behaviour prior to densification was effectively represented through ductile damage modelling, and shear damage accounted for sliding and tearing effects. These findings provide a valuable framework for evaluating and optimising newly developed composite materials for diverse engineering applications. Furthermore, the developed FE modelling approach contributes to the advancement of generalised methodologies for simulating deformation and failure in sandwich composite structures.